Silence is Golden: The Lack of Direction on Compensation for Expropriation in the 2011 Green Paper on Land Reform - du Plessis, Elmien WJ (Potchefstroom Electronic Law Journal, 2017)
The government set the target for redistribution of land to 30% by 2014. They have adopted the "willing-buyer-willing-seller" model that relies on a voluntary transaction between farmers and government to acquire such land. Frustrated at the slow pace of land reform, the ruling party is starting to indicate that the state will in future rely on its expropriation powers to acquire such land. Section 25 of the Constitution makes it clear that when the state expropriates property, compensation must be paid. The current act, the 1975 Expropriation Act, determines that such compensation must be market value, while the Constitution lists market value as only one of at least five factors that must be taken into account when determining compensation. There have been various attempts at drafting legislation that will bring compensation practices in line with the Constitution, with the latest Bill published in March 2013. This article focusses on the Green Paper that preceded the Bill, and argues that not much direction is given on how compensation for expropriation should be calculated.